Empowerment of Welding Workers at X Ltd Shipyard Batam City Through Occupational Safety and Health Education: Pemberdayaan Pekerja Pengelasan di PT X Galangan Kapal Kota Batam Melalui Edukasi Keselamatan dan Kesehatan Kerja - Irawati, Ice; Chinta Yolanda Sari; Al khudri Sembiring; Jamal, Jamal; Trisna Jayati (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2025)
Welding activities in shipyards pose risks of exposure to heat, radiation, metal fumes, and hazardous gases that can cause health problems. Initial observations show that most workers do not understand occupational safety and the proper use of PPE. This activity aims to improve welders' knowledge of occupational safety and health and provide PPE assistance. This outreach activity measures workers' knowledge before and after education using a questionnaire. Data analysis was conducted using a dependent t-test, yielding results indicating an increase in workers' knowledge after receiving OSH education, with a p-value of 0.001 < 0.05. Continuous education is necessary to enable workers to enhance their knowledge, thereby impacting safe and secure work practices at the workplace